Pemberdayaan Perempuan Melalui Pembentukan Kelompok Wanita Tani “Melati” Desa Karang Binangun Kecamatan Belitang Madang Raya - Tri Rahayu; Ayu Lestari (Jurnal Pengabdian Kepada Masyarakat, 2026)
Women's empowerment is an effort to increase family income, leading to an improvement in the quality of life and independence for women. One of the empowerment efforts for women is carried out through the agricultural sector, such as the "Melati" Women Farmer Group (KWT) in Karang Binangun Village, Belitang Madang Raya District, East OKU Regency. The purpose of this community service activity is to analyze the empowerment model and identify the women's empowerment strategies implemented by KWT Melati. This empowerment activity is analyzed using Jim Ife's empowerment strategy. The implementation method used in this community service includes a descriptive approach through socialization, agricultural skills training, group mentoring, and field program evaluation. The results of the activity show that KWT Melati applies a bottom-up empowerment model, which originates from the community, is managed by the community, and returns benefits to the community. The strategies implemented include: (1) policy and planning achieved through intensive socialization, (2) social action manifested through various productive agricultural activities on the group's land, and (3) awareness-raising and education provided through crop processing training. This activity has significant meaning in enhancing skills, economic income, and social independence for women in rural areas.